Agreement for Detecting Glaucoma Progression with the GDx Guided Progression Analysis, Automated Perimetry and Optic Disc Photography - Alencar, Luciana M. (2009)
PURPOSE: To evaluate the ability of the GDx VCC Guided Progression Analysis software (GDx-GPA) for detecting glaucomatous progression. DESIGN: Observational cohort study. PARTICIPANTS: The study included 453 eyes from 252 individuals followed for an average of 46 ± 14 months as part of the Diagnostic Innovations in Glaucoma Study (DIGS). At baseline, 29% of the eyes were classified as glaucomatous, 67% were classified as suspects and 5% as healthy eyes. METHODS: Images were obtained annually with the GDx VCC and analyzed for progression using the Fast Mode of the GDx-GPA software. Progression using conventional methods was determined by the Guided Progression Analysis software for SAP and by masked assessment of optic disc stereophotographs by expert graders. MAIN OUTCOME MEASURES: Sensitivity, specificity and likelihood ratios (LR) for detection of glaucoma progression using the GDx GPA were calculated with SAP and optic disc stereophotographs used as reference standards. Agreement among the different methods was reported using the AC1 coefficient. RESULTS: Thirty-four of the 431 (8%) glaucoma and glaucoma suspect eyes showed progression by SAP and/or optic disc stereophotographs. The GDx-GPA detected 17 of these eyes for a sensitivity of 50%. Fourteen eyes showed progression only by the GDx-GPA with specificity of 96%. Positive and negative LRs were 12.5 and 0.5, respectively. None of the healthy eyes showed progression by the GDx-GPA, with a specificity of 100% in this group. Inter-method agreement (AC(1) coefficient and 95% confidence intervals) for non-progressing and progressing eyes was 0.96 (0.94–0.97) and 0.44 (0.28–0.61), respectively. CONCLUSION: The GDx-GPA was able to detect glaucoma progression in a significant number of cases showing progression by conventional methods, with high specificity and high positive likelihood ratios. Estimates of the accuracy for detecting progression suggest that the GDx-GPA could be used to complement clinical evaluation in the detection of longitudinal change in glaucoma.